Sistem Informasi Arus Kas Berbasis Multiuser Pada PT Xpresindo Logistik Utama Semarang - Iwan Koerniawan; Ahmad Ashifuddin Aqham; Sri Wahyuni (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
PT. Xpresindo Logistik Utama Semarang Branch is a service company engaged in the expedition/delivery of goods located at Jalan Abdulrahman Saleh number 89a Semarang. Cash data processing system at PT. Xpresindo Logistik Utama Semarang Branch is simple/single, so it cannot be accessed simultaneously by other interested parties (in this case is marketing which requires an amount of money for each truck). There is still a difference between the report on the amount of road money contained in the cash flow report and the report on the amount of road money in revenue (marketing reports), this is because if there is additional road money or other costs (unloading, mell, etc.) -other) cannot be automatically added to the income statement data, and this greatly affects the accuracy of calculating the amount of profit earned by the company. The research method used is the System Development Life Cycle (SDLC) which includes planning, analysis, design, implementation and use. The new system created using MySQL Server database and Microsoft Visual Basic 6.0 Multiuser-based information system is expected to increase work productivity because it is more effective and efficient because it can be accessed by many interested parties without being limited by distance and time.